The relationship brings neonatal hypoxia and epilepsy (Research, Society and Development, 2021)
Objective: The objective of this work is to analyze the literature database on the relationship between neonatal hypoxia and epilepsy, catalog the data and provide a list of relevant works for the academic community in the health area. Methodology: this is a literature review, making a search in databases of the platforms PUBMED, Scielo and Jornal Capes, with the application of language filters, selecting english, portuguese and spanish, German for using only the works of both last five years and with bibliographic relevance. The Health Sciences Descriptors used ​​for: Neonatal Hypoxia; Epilepsy; Asphyxia. Results: scientific articles considered relevant to demonstrate the relationship between neonatal hypoxia and epilepsy, and its consequences demonstrate the need for adequate prenatal care and humanized delivery for the mother and the newborn. It is necessary for a multidisciplinary team to accompany the pregnant/parting woman, analyzing her needs and possible complications that may occur during or during childbirth.